ANALISIS PENERAPAN UPAYA EFISIENSI PENGGUNAAN KERTAS DENGAN PRINSIP 3R UNTUK MENDUKUNG PENCAPAIAN GREEN CAMPUS DI LINGKUNGAN UPN VETERAN JAKARTA TAHUN 2021 - Mutya Pratiwi, (2022)
The paper industry is one of the industries highly exploiting forest and even carrying out deforestation which plays a big role in the global warming issue. This can not be separated from the high demand of paper which is widely used in activities such as administration, where the use and production rate is often disproportionate. This study aims to analyze the application of paper use efficiency policies with 3R principles in the Administrative Subdivision of UPN Veteran Jakarta. This study is a qualitative descriptive study and uses purposive sampling for informants selection. The study results indicate that human resources for waste management (SWM); SWM budget; paper supply monitoring; education, promotion, and policies dissemination; and SWM infrastructure are inadequate. Paper reduce and reuse have been carried out, predominantly by utilizing technology, but the absence of recycling facilities has hampered the paper recycle. Furthermore, paper waste is still found despite the efforts been done. The paper use efficiency as mandated in Rector's Regulation Number 53 of 2019 concerning the Go Green Campus Implementation UPN Veteran Jakarta has not been fully achieved. UPN Veteran Jakarta can improve every component of the paper use efficiency efforts including letters/archives technology and also recycling technology.